2021
DOI: 10.1002/1873-3468.14186
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the non‐ATP‐binding pocket of the MAP kinase p38γ mediates a novel mechanism of cytotoxicity in cutaneous T‐cell lymphoma (CTCL)

Abstract: We describe here for the first time a lipid‐binding‐domain (LBD) in p38γ mitogen‐activated protein kinase (MAPK) involved in the response of T cells to a newly identified inhibitor, CSH71. We describe how CSH71, which binds to both the LBD and the ATP‐binding pocket of p38γ, is selectively cytotoxic to CTCL Hut78 cells but spares normal healthy peripheral blood mononuclear (PBMC) cells, and propose possible molecular mechanisms for its action. p38γ is a key player in CTCL development, and we expect that the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…In both these structures the αG-helices interaction is very similar, as well as the relative orientation of the kinases. Several studies have shown that small molecules can target this region (32)(33)(34)(35)(36) and modulate the position of the MAPK insert helices (Fig. S6).…”
Section: Engagement With Substratementioning
confidence: 99%
“…In both these structures the αG-helices interaction is very similar, as well as the relative orientation of the kinases. Several studies have shown that small molecules can target this region (32)(33)(34)(35)(36) and modulate the position of the MAPK insert helices (Fig. S6).…”
Section: Engagement With Substratementioning
confidence: 99%
“…p38γ MAPK has been shown to regulate cell cycle transition, cell mobility, metastasis, EMT, CSC population, and tumorigenesis ( 10 , 36 39 ). Importantly, p38γ MAPK is overexpressed and implicated in several types of cancers including colorectal cancer, liver cancer, pancreatic cancer, and breast cancer ( 16 , 37 , 40 , 41 ); increased p38γ MAPK expression predicts a poor clinical prognosis ( 18 , 36 ). CSCs are a subpopulation of tumor cells capable of self-renewal and differentiation and involved in tumor initiation, recurrence, progression, chemoresistance and metastasis ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In both these structures, the αG-helices interaction is very similar, as well as the relative orientation of the kinases. Several studies have shown that small molecules can target this region in p38 isoforms ( 37 41 ) and modulate the position of the MAPK-insert helices (fig. S7).…”
Section: Discussionmentioning
confidence: 99%
“…2, A, C, and D, and movie S2), which clamps the MKK6 αG helix upon binding (movie S3). This insert has been described as a lipid-binding site important in regulation ( 35 , 36 ), and several studies have identified small molecules that target this pocket ( 37 41 ) (fig. S7).…”
Section: Architecture Of the Mkk6-p38α Complexmentioning
confidence: 99%